PENERAPAN TEKNIK PENGONDISIAN AVERSI DALAM KONSELING BEHAVIORAL UNTUK MENURUNKAN PERILAKU MALADAPTIF PADA SISWA SMK PGRI 1 DENPASAR - I Nyoman Rajeg Mulyawan (Widyadari : Jurnal Pendidikan, 2022)
This study aims to determine the decrease in maladaptive behavior after applying aversion conditioning techniques to students at SMK PGRI 1 Denpasar. This research is focused on students who have high maladaptive behavior. The research subjects were students of class VII Automotive, totaling 25 people. To obtain data, a maladaptive behavior scale was used. The results of the initial study showed that there were 5 students with high maladaptive behavior. From the first cycle of action there was a decrease in students' maladaptive behavior on average from 77.4% to 69.6%. The decrease was still in the high category so the research was continued in cycle II. The results obtained in the second cycle by making improvements in terms of planning and counseling process obtained students' maladaptive scores decreased on average from 69.6% to 62%. There was 1 student whose maladaptive behavior decreased to the low category but overall was still in a position with a moderate category. Changes in behavior do take quite a long time as a person's personality develops. Thus, it can be concluded that the application of aversion conditioning counseling techniques in behavioral counseling can reduce the maladaptive behavior of SMK PGRI 1 Denpasar students in 2021. It is recommended for guidance and counseling teachers to use aversion conditioning counseling techniques when handling cases with maladaptive behavior.